Investigation of self-reported chronic urticaria among adults in grasslands of northern China. Issue 47 (20th November 2020) - Chen, Yan-Lei; Shi, Hai-Yun; Ma, Ting-Ting; Wang, Xue-Yan
Abstract : Abstract: The clinical epidemiological characteristics of chronic urticaria (CU) in different populations were not completely consistent, and the epidemiological characteristics of CU were very complex. At present, there were some patient-based studies on CU, but few natural population-based studied in the world. This study aimed to analysis the prevalence of self-reported CU among adults in grasslands of northern China and its closely related factors. A multistage and proportionately stratified random sampling with a field interviewer-administered survey study was performed together with skin prick tests (SPT) and measurements of the daily pollen count. A total of 3406 subjects completed the study. The prevalence of self-reported CU was 5.61% (n = 191), which was higher in women than that of men (6.91% vs 4.08%, X 2  = 12.785, P  < .001). Seasonal or seasonal aggravation CU accounted for 110 (57.59%) patients. Pollen dispersal season was basically consistent with the peak season of CU, but there was no significant difference in the positive rate of pollen SPT between CU with seasonal or seasonal aggravation symptom and CU with free of symptom ( X 2  = 0.425, P  = .51), as well as between CU with seasonal or seasonal aggravation symptom and perennial CU ( X 2  = 0.439, P  = .51). Eczema (odds ratio [OR] = 2.807, P  < .001), chronic diarrhea (OR = 2.486, P  < .01), food allergy history (OR = 1.890, P  < .01), history of family allergy (OR = 1.800, P  < .001), and conjunctivitis (OR = 1.749, P  < .01) were closely related to CU. This investigation provided the factors closely related to CU, and provided certain ideas for further research on the etiology and prevention of CU. Abstract : Supplemental Digital Content is available in the text